What Values Should Count in the Arts? The Tension between Economic Effects and Cultural Value - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2005)
The basic distinction made in this volume compares "economic value", expressed in monetary terms, to "cultural value", reflecting cultural, aesthetic and artistic significance. This paper makes a different distinction which is rarely made explicit but which is of central importance to the decision process in cultural policy. On the one hand, ?value? is attached to the economic effects of cultural activities: When cultural values are created, economic activity is bolstered. The increase of commercial actitivities induced is measured by the so-called "impact effect". On the other hand, the value of culture is reflected in the increased utility going to consumers and non-consumers of a particular cultural activity. This type of value is measured by "willingness to pay studies". I argue that these two values dominate cultural policy but they capture totally different aspects and are proferred by different kinds of communities.
Keywords: 330